Music Effect Studies in The Experience of Playing Video Games with Qualitative and Quantitative Approaches - Wibowo, Tony (JITE (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING), 2019)
This research is conducted to determine how music affects the video game experience. Effect of music in video game is considered important in building emotion and scene in video game but always considered below graphics and gameplay importance, moreover they are rarely a scientific approach to prove how music of video game affect its player. This research uses qualitative approach using experimental method; and quantitative approach to further prove the correlation. The experiment uses three games with four music variation, each consisting of 30 participants. The game we used are agar.io, Dots, Typing Challenge. Result of the experiment shows that music is able affects gaming performance is positively depending on genre of video game. Questionnaire response from every participant indicate that music has a strong correlation to video game experience and gamer?s performance. Music affect significantly performance in Games that design to be fast paced and quick reaction; but not really shown in slow paced and tactical approached games. Further study needs to be conducted to see how the video game music affecting player combined with other elements of video game.